2020
DOI: 10.1021/acs.inorgchem.0c00944
|View full text |Cite
|
Sign up to set email alerts
|

Two Metal–Organic Frameworks Based on Hexanuclear Cobalt–Hydroxyl Clusters or a Manganese–Hydroxyl Chain from Triangular [MII33-OH)] (M = Co and Mn) Units: Antiferromagnetic and Spin-Canting Antiferromagnetic Ordering with Soft-Magnetic Behavior

Abstract: Three-dimensional highly connected isonicotinic acid−base metal−organic frameworks (MOFs), [Co II 6 (μ 3 -OH) 2 (in) 7 (HCOO) 3 H 2 O]•4DMF (1) and [Mn II 3 (μ 3 -OH)-(in) 3 (CH 3 COO) 2 ] (2) (Hin = isonicotinic acid), have been successfully prepared. Compounds 1 and 2 were constructed from planar Co 6 cluster SBUs or rare 1D manganese-hydroxyl chain SBUs, respectively. Both SBUs contain triangular M II 3 (OH) (M = Co and Mn) central units, which are connected by rare syn,anti,syn,anti-and syn,syn,anti-coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…where the best parameters are J 1 /k B = 2.01(9), J 2 /k B = 0.18(6), g = 2.10, and zJ′/k B = −0.72 (8). It is important to note that the resulting g value is very much in line with the Ni(II) compound.…”
Section: ■ Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…where the best parameters are J 1 /k B = 2.01(9), J 2 /k B = 0.18(6), g = 2.10, and zJ′/k B = −0.72 (8). It is important to note that the resulting g value is very much in line with the Ni(II) compound.…”
Section: ■ Introductionmentioning
confidence: 85%
“…Metal–organic frameworks (MOFs) have attracted much attention as a functional material in recent years. This is not only because of their intriguing structures but also because of their potential applications in the fields of luminescence, catalysis, adsorption, proton conduction, and so on. In particular, MOFs are excellent candidates to study the elusive magnetostructural correlations and some fundamental magnetic phenomena, such as spin-canting, spin-frustration, metamagnetism, single-molecule magnets, and so on. …”
Section: Introductionmentioning
confidence: 99%
“…This markedly field-dependent behavior is typical for spin-canting. 36,37 Comparing {Co 24 } to {Co 14 } and {Co 12 Cd 12 }, we found that the magnetic behavior of {Co 24 } was more markedly field-dependent than {Co 14 }, suggesting the local spin-canting configuration in {Co 24 }. While external Co 2+ was replaced by Cd 2+ , the canted behavior had been suppressed.…”
Section: ■ Experimental Sectionmentioning
confidence: 96%